“The prohibition of euthanasia” and medical oaths of Hippocratic Stemma - Merino, Sabrina; Aruanno, María E.; Gelpi, Ricardo J.; Rancich, Ana M. (Acta Bioethica, 2017)
It has been debated whether the Hippocratic Oath’s commitment referring to not administering poisonous/ deadly drugs prohibits: euthanasia, assisted suicide or murder. The first goal was to analyze if the prohibition of administering poisonous/deadly drugs was kept and how it changed in medical oaths of Hippocratic stemma of different time periods and religious orientations. The second aim was discern what is forbidden: euthanasia, assisted suicide or murder. Seventeen medical oaths: 4 Medieval, 2 Modern and 11 Contemporary oaths were studied and divided into those expressing the commitment like the original, those that may include it depending on the interpretation and those that do not mention it. Medieval and Modern oaths express it similarly to the Hippocratic Oath, possibly due to religious and Hippocratic/Galenic influences. What they forbid cannot be inferred. Contemporary oaths maintaining the commitment tend to include phrases regarding active euthanasia and assisted suicide. Other contemporary oaths may generalize it. It would be advisable that medical oaths would contain clear and specific premises regarding this commitment depending on the country, school and the student body’s idiosyncrasies.